2021
DOI: 10.1136/svn-2020-000744
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sex-specific differences in the carotid revascularisation literature: findings from a scoping review

Abstract: ObjectiveNo systematic review of the literature has dedicated itself to looking at the management of symptomatic carotid stenosis in female patients. In this scoping review, we aimed to identify all randomised controlled trials (RCTs) that reported sex-specific outcomes for patients who underwent carotid revascularisation, and determine whether sufficient information is reported within these studies to assess short-term and long-term outcomes in female patients.Design, setting and participantsWe systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Currently, surgical revascularization (EC-IC bypass) improves cerebral hemodynamics and oxygen extraction fraction and is used as a primary treatment option for patients with CICAO ( 19 , 20 ). However, a large-scale cohort study showed that most patients with CICAO are not suitable for EC-IC bypass ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, surgical revascularization (EC-IC bypass) improves cerebral hemodynamics and oxygen extraction fraction and is used as a primary treatment option for patients with CICAO ( 19 , 20 ). However, a large-scale cohort study showed that most patients with CICAO are not suitable for EC-IC bypass ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%